Sunlight exposure in infancy decreases risk of sporadic retinoblastoma, extent of intraocular disease. Issue 6 (7th May 2021) - Orjuela‐Grimm, Manuela; Carreño, Silvia Bhatt; Liu, Xinhua; Ruiz, Ambar; Medina, Paola; Ramirez Ortiz, Marco A.; Rendon, Josefina Romero; Molina, Norma Citlali Lara; Pinilla, Hector; Hinojosa, Daniela; Rodriguez, Laura; Connor, Anita O'; et al.
Abstract: Background: Prior ecologic studies suggest that UV exposure through sunlight to the retina might contribute to increased retinoblastoma incidence. Aims: Our study objectives were (1) to examine the relationship between exposure to sunlight during postnatal retinal development (prior to diagnosis of sporadic disease) and the risk of retinoblastoma, and (2) to examine the relationship between sun exposure during postnatal retinal development, and the extent of disease among children with unilateral and bilateral retinoblastoma. Methods and results: We interviewed 511 mothers in the EpiRbMx case‐control study about their child's exposure to sunlight during postnatal retinal cell division by examining three time periods prior to Rtb diagnosis coinciding with developmental stages in which outdoor activities vary. Weekly sun exposure was compared by age period, between unilateral ( n = 259), bilateral ( n = 120), and control ( n = 132) children, accounting for two factors affecting UV exposure: residential elevation and reported use of coverings to shield eyes. For cases, association between sunlight exposure and clinical stage was examined by laterality at each age period. After adjusting for maternal education and elevation, sun exposure was lower in cases than controls in all three age periods especially during the first 6 months, and in children 12–23 months whose mothers did not cover their eyes when outdoors. In children diagnosed after 12 months of age, sun exposure during the second year of life (age 12–23 months) appeared inversely correlated (r = −0.25) with more advanced intraocular disease in bilateral Rtb children after adjusting for maternal education, residential elevation, and age of diagnosis ( p < .09) consistent with effects of Vitamin D exposure on intraocular spread in earlier transgenic murine models of retinoblastoma, and suggesting potential chemopreventive strategies. Conclusion: Sun exposure in early childhood is protective for retinoblastoma and may decrease degree of intraocular spread in children with bilateral Rtb.